2019
DOI: 10.1186/s12913-018-3759-5
|View full text |Cite|
|
Sign up to set email alerts
|

Amputation rates of the lower limb by amputation level – observational study using German national hospital discharge data from 2005 to 2015

Abstract: BackgroundIn international comparisons, rates of amputations of the lower limb are relatively high in Germany. This study aims to analyze trends in lower limb amputations over time, as well as outcomes of care concerning in-hospital mortality and reamputation rates during the same hospital stay which might indicate the quality of surgical and perioperative health care processes.MethodsThis work is an observational population-based study using complete national hospital discharge data (Diagnosis-Related Group S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
2
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 27 publications
9
56
2
15
Order By: Relevance
“…In our study, the overall and yearly age-standardized rate of major LEA was signi cantly higher in males than females. Similar to our results, the analysis of national data of Germany noted higher amputation rates in males compared to females between 2005 and 2015 [12]. Another study from Germany reported signi cantly higher rates of amputations in males with and without diabetes compared to females that were independent of healthcare-related factors [21].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the overall and yearly age-standardized rate of major LEA was signi cantly higher in males than females. Similar to our results, the analysis of national data of Germany noted higher amputation rates in males compared to females between 2005 and 2015 [12]. Another study from Germany reported signi cantly higher rates of amputations in males with and without diabetes compared to females that were independent of healthcare-related factors [21].…”
Section: Discussionsupporting
confidence: 90%
“…The temporal trend of major LEA re ects the performance of the primary healthcare system regarding the long-term care of diabetes. As mentioned earlier, the reduction in the incidence of major LEA in individuals with diabetes has been witnessed worldwide [12,13], however, an interesting temporal trend for LEA has been observed in Austria as per OECD estimates. .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In Germany, the proportion of age-adjusted major amputations (above-ankle to hemipelvectomy) with diagnosed diabetes mellitus declined by 30.9% within 9 years (2005-2014), whereas minor amputations in this cohort increased by 25.4%. [1] Another publication reported comparable trends for the period 2005-2015: − 43% for hip joint/femoral amputation and − 36.9% for knee and lower leg amputation [2].…”
Section: Introductionmentioning
confidence: 94%
“…We identified one German study that reported midterm survival of lower limb amputees [21]. Other German studies only reported in-hospital-mortality [2]. Icks et al [21] provided survival data for patients with and without DM up to 5 years after amputation.…”
Section: Epidemiologymentioning
confidence: 99%